2021
DOI: 10.1029/2021ja029966
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Dependence of Polarization Reversal Effects on the Particle Pitch Angle Scattering by EMIC Waves

Abstract: EMIC waves can pitch angle scatter radiation belt electrons and ring current protons rapidly into the loss cone via cyclotron resonance, leading to the electron dropout in the radiation belts and proton aurora at subauroral latitudes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…(2020) and Lou et al. (2021) further confirmed that inclusion of polarization reversal of EMIC waves at higher latitudes weakens the pitch angle scattering efficiency of ring current protons. Furthermore, proton precipitations into the atmosphere due to EMIC wave scattering can result in the formation of detached proton arcs at subauroral latitudes (Fuselier et al., 2004; Spasojevic et al., 2011; Su et al., 2011) and the reversed energy‐latitude type of ion precipitation boundary (Cao et al., 2016; Liang et al., 2014), as well as local density disturbances in the E‐region (∼100–150 km) ionosphere (Tian et al., 2023).…”
Section: Introductionmentioning
confidence: 77%
“…(2020) and Lou et al. (2021) further confirmed that inclusion of polarization reversal of EMIC waves at higher latitudes weakens the pitch angle scattering efficiency of ring current protons. Furthermore, proton precipitations into the atmosphere due to EMIC wave scattering can result in the formation of detached proton arcs at subauroral latitudes (Fuselier et al., 2004; Spasojevic et al., 2011; Su et al., 2011) and the reversed energy‐latitude type of ion precipitation boundary (Cao et al., 2016; Liang et al., 2014), as well as local density disturbances in the E‐region (∼100–150 km) ionosphere (Tian et al., 2023).…”
Section: Introductionmentioning
confidence: 77%
“…In addition, the pitch angle scattering efficiency may be affected by its polarization property. Previous simulation studies have shown that polarization reversal of H + ‐band EMIC waves could cause more efficient scattering of relativistic electrons (e.g., Cao et al., 2020; Lou et al., 2021). As shown in Figures 2e and 2f, the first and the third EMIC waves are linearly polarized, while the second EMIC wave is left‐hand polarized with smaller wave normal angles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhu et al (2020) reported a compression-induced EMIC wave event and provided direct evidence of pitch angle scattering of relativistic electrons by EMIC waves. In addition, a variety of studies tried to figure out the factors that influence the pitch angle scattering efficiency of relativistic electrons by EMIC waves and find that plasma wave parameters can affect the wave-particle interaction between EMIC waves and relativistic electrons, such as wave amplitude, the ellipticity of polarization, wave normal angle and wave frequency (Cao et al, 2020;Lou et al, 2021;Qin et al, 2020;Silin et al, 2011;. Cao et al (2020) conducted a simulation study and concluded that polarization reversal has an important impact on the pitch angle diffusion coefficients induced by H + -band EMIC waves, but not He + -band EMIC waves.…”
mentioning
confidence: 99%